Secure and resilient software : requirements, test cases, and testing methods - Merkow, Mark S.; Raghavan, Lakshmikanth (CRC Press, 2012)
Secure and Resilient Software: Requirements, Test Cases, and Testing Methods provides a comprehensive set of requirements for secure and resilient software development and operation. It supplies documented test cases for those requirements as well as best practices for testing nonfunctional requirements for improved information assurance. This resource-rich book includes: Pre-developed nonfunctional requirements that can be reused for any software development project Documented test cases that go along with the requirements and can be used to develop a Test Plan for the software Testing method